Physical Quality of Kitchen Lemongrass Powder (Cymbopogon citratus L.) Result of Convection Oven Drying - Dian Purbasari; Anisa Dimas Anggraini (Protech Biosystems Journal, 2022)
Lemongrass is one of the grass plants that can be cultivated inIndonesia. lemongrass has benefits as a food fragrance by processing it directlyinto the dish. The parts of lemongrass that are used as food fragrances are thestems and leaves. The use of lemongrass can be developed if it is processedproperly. One way of processing it is to make lemongrass powder in the so that ithas a longer and practical shelf life. The process used to make lemongrass powderis the drying process using a convection oven. The purpose of this study was todetermine the drying process of lemongrass using a convection oven with the effectof temperature differences and drying duration and to determine the physicalquality of lemongrass powder. The result of this research is that the water contentin lemongrass powder is <12% with the physical quality of the color brightness (L)at a temperature of 60℃ and a drying duration of 22 hours getting the highestvalue of 76.05. The highest value of reddish color (a) is 5.88 at a temperature of80℃ and a duration of 20 hours. The highest value of yellowish color (b) is 16.23at a temperature of 60℃ and a duration of 22 hours. The highest bulk density is0.54 g/cm3 at 70℃ and a duration of 22 hours. The highest water absorptioncapacity is 5.44 ml/g at 60℃ and 18 hours duration. The highest stack angle is40.69˚ at a temperature of 60℃ and a duration of 18 hours.